2005
DOI: 10.1002/cne.20551
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of EphA3 at both the RNA and protein level in the developing mammalian forebrain

Abstract: The ephrin/Eph system is well known to regulate various aspects of brain development. In this study, we analyzed the expression profiles of EphA3 at both the RNA and protein level in developing mouse forebrains. Although the EphA3 gene is known to encode two isoforms of the receptors, a full-length transmembrane form, and a short, secretory form, only the full-length isoform was detected in the developing forebrain. We found that, in the early developmental stages, while EphA3 mRNA was expressed in the dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
(26 reference statements)
5
27
0
Order By: Relevance
“…This suggests that ephrinA5 and its receptors are not expressed in complementary gradient as it has been described for other systems such as the retinotectal one [8,44]. Instead, we showed that ephrinA5 is uniformly expressed in this structure as for its receptors [40-42,35,20]. This ligand-receptor interaction may result in an attraction of the cells, thus regulating the connections of mitral cells.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This suggests that ephrinA5 and its receptors are not expressed in complementary gradient as it has been described for other systems such as the retinotectal one [8,44]. Instead, we showed that ephrinA5 is uniformly expressed in this structure as for its receptors [40-42,35,20]. This ligand-receptor interaction may result in an attraction of the cells, thus regulating the connections of mitral cells.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, ephrins are known to be involved in cell migration and boundary formation in other nervous systems [2,3], and at this stage the cell body of developing mitral cells appears to transform from tangential to radial orientation with rearrangement of its microtubules structure [39]. Moreover, the presence of potential ephrinA5 receptors such as EphA3 [40], EphB2 [41], EphA5 [35,42,43], EphA7 and EphA4 [35] has been also described in the mitral cells during embryogenesis. This suggests that ephrinA5 and its receptors are not expressed in complementary gradient as it has been described for other systems such as the retinotectal one [8,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A,C; supplementary material Fig. S7A,C,E,G,I,K,M,O; Kudo et al, 2005). In the age-matched Olig2-KO forebrain, the Epha3-and Epha5-expressing TE was dorsally expanded and, conversely, the Ephas-negative prethalamus were reduced in size ( Fig.…”
Section: Disorganized Tcas Extend From Non-olig2 Lineage Cellsmentioning
confidence: 92%
“…These studies have found EphB2 fusion protein and EphB3 mRNA expression in the CC during the development of this tract Orioli et al, 1996), which occurs between embryonic day 15 (E15) and E18 in the mouse CNS (Rash and Richards, 2001). In addition, EphA receptors were also detected in CC fibers, suggesting a possible function for these molecules in CC development (Kudo et al, 2005). Analysis of EphB2 knock-out (EphB2 KO ) and EphB3 KO mice supported a role for Eph receptors in CC and AC midline pathfinding Orioli et al, 1996).…”
Section: Introductionmentioning
confidence: 88%